A invenção do patrimônio: memória e identidade no tombamento de São Luiz do Paraitinga como patrimônio nacional - Daniel Messias dos Santos; André Luiz da Silva (Ciências Sociais Unisinos)
The article discusses the concept of heritage using theoretical references on the subject and also primary sources through testimonies whose focus is the designation of material and immaterial goods as national heritage in São Luiz do Paraitinga, São Paulo. The aim is to foster debate on heritage on the basis of decisions made by bodies such as the Institute of Historical and Artistic Heritage (IPHAN) and the Council for the Defense of the Historical, Archaeological, Artistic and Touristic Heritage (CONDEPHAAT) and by the community of São Luiz do Paraitinga during the reconstruction of the historic city, after the 2010 flood that destroyed much of the architectural ensemble of the city. Methodologically the authors used semi-structured interviews, the ethnographic account and for analyzing the method of data triangulation.